In situ forming implants: Component, formation mechanisms, and pharmaceutical applications - Keyang Ni; Haojie Yu; Li Wang; Yuan Meng (Chemical Engineering Journal, 2026)

Cellulose/polyester-blended microplastics amplify plastisphere pathogen and antibiotic resistome risks - Keyang Jiang; Xinru Pan; Sijia Zhu; Zewen Dang; Zhenzhen Yang; Liangyu Huang; Xiaochen Pan; Xuelian Zou; Jian Zhang; Yanzhu Guo; Wei Zhang; Zhi Li; et al. (Bioresource Technology, 2026)

Associations between domestic water hardness and incident type 2 diabetes and the mediating role of metabolomics - Hanwen Zhou; Sicheng Li; Keyang Li; Wenlong Li; Yingcheng Liu; Rui Yu; Xufeng Xian; Wei Zheng; Xiaoni Zhong; Biao xie (Environmental Pollution, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Corrigendum to “Amphiphilic colloidal particles/Ca2+ reinforced edible agar nanocomposite film by multiple cross-linking/microphase separation strategies” [Food Hydrocolloids, (159), February 2025, 110602] - Qingmei Zhu; Xiaona Su; Keyang Mai; Riting Huang; Shujuan Yang; Haifang Liu; Furui He; Yu Bao; Gaobo Yu; Yuhong Feng; Jiacheng Li (Food Hydrocolloids, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Unveiling role of accumulation by various submerged plants in removal of per- and polyfluoroalkyl substances from reclaimed water - Lin Chen; Qian Wang; Yuanyuan Li; Xin Shan; Keyang Wu; Cuizhu Sun; Lingyun Chen; Fengmin Li (Bioresource Technology, 2025)

Nacre-inspired gradient design and multifunctional wood-based composites using recycled GFRP from decommissioned wind turbine blades - Hualei Zhang; Yao Du; Dan Lu; Keyang Liu; Tiantian Zhang; Xiaohai Chen; Hongguang Liu; Li Li; Bin Luo (Chemical Engineering Journal, 2025)

Longitudinal reconfiguration of multifaceted fish α and β diversity triggered by non-native species invasion in tropic rivers of Hainan Island - Dangen Gu; Chi Zhang; Gaojun Li; Meng Xu; Hui Wei; Miao Fang; Lu Shu; Xuejie Wang; Keyang Peng; Zhongguan Jiang; Fandong Yu (Journal of Environmental Management, 2025)

Mitigating nitrobenzene toxicity in anaerobic digestion using hollow carbon spheres: Enhanced methane production via direct interspecies electron transfer - Shunan Zhao; Keyang Li; Shaoqing Zhu; Qianli Guo; Ge Song; Kai Zhao; Qianming Gong; Ruiping Liu (Journal of Water Process Engineering, 2025)

Amphiphilic colloidal particles/Ca2+ reinforced edible agar nanocomposite film by multiple cross-linking/microphase separation strategies - Qingmei Zhu; Xiaona Su; Keyang Mai; Riting Huang; Shujuan Yang; Haifang Liu; Furui He; Yu Bao; Gaobo Yu; Yuhong Feng; Jiacheng Li (Food Hydrocolloids, 2025)

Dynamic host–guest/π–π multiple bonds of alginate-based super-amphiphiles reinforced the mechanical stability and foliar deposition of jammed emulsion droplet - Shujuan Yang; Furui He; Keyang Mai; Yan Zhou; Chaonan Shang; Haifang Liu; Yuhong Feng; Gaobo Yu; Jiacheng Li (Chemical Engineering Journal, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Exogenous signaling molecules N-acyl-homoserine lactones promotes the reconstruction of sludge particles after impact with highly concentrated urea-formaldehyde resin microplastics - Keyang Jiang; Xiao Yang; Qian Gao; Junxia Ni; Jinhu Feng; Di Wu; Xuelian Zou; Li Hu; Xi Liu; Zhaoping Song; Zhiwei Wang (Journal of Environmental Management, 2024)

Surface free radicals activated CoP/MoS2 sensors through electrocatalytic water splitting for enhanced NO2 sensing at room temperatures - Xixi Li; Xiao Wang; Zhaokun Sun; Feifei Li; Yao Fu; Keyang Zhao; Gang Zhao; Cunguang Zhu; Xijin Xu (Chemical Engineering Journal, 2024)

B ← N coordination bond reinforced dynamic fluorescence of pH-responsive amphiphile alginate aggregates for anti-counterfeiting - Riting Huang; Furui He; Shujuan Yang; Keyang Mai; Shuntian Huang; Haifang Liu; Yuhong Feng; Gaobo Yu; Jiacheng Li (Carbohydrate Polymers, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

Changes in the structure and functional properties of soybean isolate protein: Effects of different modification methods - Lu Han; Jinlong Li; Yitong Jiang; Keyang Lu; Panpan Yang; Lianzhou Jiang; Yang Li; Baokun Qi (Food Chemistry, 2024)

Ros-responsive dextran-phenylboronic acid-silibinin nanoparticles for targeting delivery of BAPTA-AM to effectively eliminate calcium overload-mediated inflammatory cascades and mitochondrial apoptosis: Alleviating acute liver injury - Yanan Wang; Huichao Wei; Keyang Li; Liru Liu; Yingfei Zhu; Xinyuan Wang; Jiahui Yan; Liangmin Yu; Xuefeng Yan; Zhiyu He (Chemical Engineering Journal, 2024)

Multi-bioinspired alginate-based gel coatings formed by dynamic metal–ligand assembly for enhancing foliar affinity and rain-fastness of pesticides - Keyang Mai; Shujuan Yang; Xinyu Zhao; Riting Huang; Shuntian Huang; Congying Xu; Gaobo Yu; Yuhong Feng; Jiacheng Li (Chemical Engineering Journal, 2024)

Novel Selective Quantification of Zinpentraxin Alfa Biotherapeutic in the Presence of Endogenous Isomer in Plasma Samples of Idiopathic Pulmonary Fibrosis Patients Using Immunoaffinity LC–MS - Maoyin Li; Audrey Arjomandi; Xiaowei Sun; Erhu Lu; Tulika Tyagi; WeiYu Lin; Saloumeh K. Fischer; Surinder Kaur; Keyang Xu (The AAPS Journal, 2023)
Idiopathic pulmonary fibrosis (IPF) is a progressive fatal interstitial lung disease that affects three million patients worldwide and currently without an effective cure. Zinpentraxin alfa, a recombinant human pentraxin-2 (rhPTX-2) protein, has been evaluated as a potential drug candidate for the treatment of IPF. Clinical pharmacokinetic analysis of zinpentraxin alfa has been challenging historically due to interference from serum amyloid P component (SAP), an endogenous human pentraxin-2 protein. These molecules share an identical primary amino acid sequence and glycan composition; however, zinpentraxin alfa possesses α2,3-linked terminal sialic acid residues while SAP is an α2,6-linked isomer. By taking advantage of this only structural difference, we developed a novel assay strategy where α2,3-sialidase was used to selectively hydrolyze α2,3-linked sialic acid residues, resulting in desialylated zinpentraxin alfa versus unchanged sialylated SAP, following an immunoaffinity capture step. Subsequent tryptic digestion produced a unique surrogate asialo-glycopeptide from zinpentraxin alfa and allowed specific quantification of the biotherapeutic in human plasma. In addition, a common peptide shared by both molecules was selected as a surrogate to determine total hPTX-2 concentrations, i.e., sum of zinpentraxin alfa and SAP. The quantification methods for both zinpentraxin alfa and total hPTX-2 were validated and used in pharmacokinetic assessment in IPF patients. The preliminary results suggest that endogenous SAP levels remained largely constant in IPF patients throughout the treatment with zinpentraxin alfa. Our novel approach provides a general bioanalytical strategy to selectively quantify α2,3-sialylated glycoproteins in the presence of their corresponding α2,6-linked isomers. Graphical Abstract

Ambient PM2.5, ozone and mortality in Chinese older adults: A nationwide cohort analysis (2005–2018) - Yunquan Zhang; Zhouxin Yin; Shaojie Li; Junfeng (Jim) Zhang; Haitong Zhe Sun; Keyang Liu; Kokoro Shirai; Kejia Hu; Chengxuan Qiu; Xiaoyun Liu; Yachen Li; Yi Zeng; et al. (Journal of Hazardous Materials, 2023)

Construction and characterization of Pickering emulsions stabilized by soy protein hydrolysate microgel particles and quercetin-loaded performance in vitro digestion - Jinjie Yang; Bin Zhu; Keyang Lu; Jingjing Dou; Yijie Ning; Huan Wang; Yang Li; Baokun Qi; Lianzhou Jiang (Food Research International, 2023)

Tuning interfacial microstructure of alginate-based amphiphile by dynamic bonding for stabilizing Pickering emulsion - Shuntian Huang; Zhaojun Wang; Qichang Zhou; Shujuan Yang; Riting Huang; Keyang Mai; Wenqi Qin; Junhao Huang; Gaobo Yu; Yuhong Feng; Jiacheng Li (Carbohydrate Polymers, 2023)

Light-tuning the host–guest interfacial recognition of Alginate-based amphiphiles for oil-in-water droplet deposition - Xinyu Zhao; Qu Zeng; Shujuan Yang; Furui He; Wenqi Qin; Zhaojun Wang; Keyang Mai; Gaobo Yu; Junhao Huang; Jiacheng Li; Yuhong Feng (Chemical Engineering Journal, 2023)

Efficient selective adsorption of cytokine IL-6 and other middle-macromolecular toxins in the serum of uremia patients with specially designed porous hollow carbon spheres - Xiaohuan Zhao; Chong Wang; Boyang Xu; Jie Liang; Keyang Li; Yiqing Guo; Ming Gong; Yun Zhao; Yilun Huang; Yuehong Li; Ming Zhao; Daming Zhuang; et al. (Chemical Engineering Journal, 2023)

In vitro simulated digestion of and microbial characteristics in colonic fermentation of polysaccharides from four varieties of Tibetan tea - Yaowen Tan; Meiwen Li; Keyang Kong; Yushan Xie; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Xinjie Hu; Caixia Wang; Saiyan Chen; Wenjuan Wu; et al. (Food Research International, 2023)

Light-dimerization telechelic alginate-based amphiphiles reinforced Pickering emulsion for 3D printing - Xinyu Zhao; Shujuan Yang; Furui He; Haifang Liu; Keyang Mai; Junhao Huang; Gaobo Yu; Yuhong Feng; Jiacheng Li (Carbohydrate Polymers, 2023)

Spatial distribution of atmospheric bioaerosols in Beijing, Hangzhou and Wuhan, China - Xuezheng Ma; Qi Zhang; Keyang Liu; Liping Zhang; Manman Zhang; Xin Zhao; Chunya Zhou; Jinke Li; Ming Cheng; Lili Li; Kongxin Hu; Jinsong Li; et al. (Aerobiologia, 2021)

Abnormal Brain Structure and Function in First-Episode Childhood- and Adolescence-Onset Schizophrenia: Association with Clinical Symptoms - Yanhong Xia; Dan Lv; Yinghui Liang; Haisan Zhang; Keyang Pei; Rongrong Shao; Yali Li; Yan Zhang; Yuling Li; Jinghua Guo; Luxian Lv; Suqin Guo (Neuroscience Bulletin, 2019)

Reduction of pentavalent antimony by trypanothione and formation of a binary and ternary complex of antimony(III) and trypanothione - Siucheong Yan; Fei Li; Keyang Ding; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2003)